A Digital Intervention for Primary Care Practitioners to Support Antidepressant Discontinuation (Advisor for Health Professionals): Development Study - Bowers, Hannah; Kendrick, Tony; van Ginneken, Nadja; Glowacka, Marta; Williams, Samantha; Leydon, Geraldine M; May, Carl; Dowrick, Christopher; Moncrieff, Joanna; Johnson, Chris F; Moore, Michael; Laine, Rebecca; et al. (Journal of medical Internet research, 2021)
The number of people receiving antidepressants has increased in the past 3 decades, mainly because of people staying on them longer. However, in many cases long-term treatment is not evidence based and risks increasing side effects. Additionally, prompting general practitioners (GPs) to review medication does not improve the rate of appropriate discontinuation. Therefore, GPs and other health professionals may need help to support patients discontinuing antidepressants in primary care. This study aims to develop a digital intervention to support practitioners in helping patients discontinue inappropriate long-term antidepressants (as part of a wider intervention package including a patient digital intervention and patient telephone support). A prototype digital intervention called Advisor for Health Professionals (ADvisor HP) was planned and developed using theory, evidence, and a person-based approach. The following elements informed development: a literature review and qualitative synthesis, an in-depth qualitative study, the development of guiding principles for design elements, and theoretical behavioral analyses. The intervention was then optimized through think-aloud qualitative interviews with health professionals while they were using the prototype intervention. Think-aloud qualitative interviews with 19 health professionals suggested that the digital intervention contained useful information and was readily accessible to practitioners. The development work highlighted a need for further guidance on drug tapering schedules for practitioners and clarity about who is responsible for broaching the subject of discontinuation. Practitioners highlighted the need to have information in easily and quickly accessible formats because of time constraints in day-to-day practice. Some GPs felt that some information was already known to them but understood why this was included. Practitioners differed in their ideas about how they would use ADvisor HP in practice, with some preferring to read the resource in its entirety and others wanting to dip in and out as needed. Changes were made to the wording and structure of the intervention in response to the feedback provided. ADvisor HP is a digital intervention that has been developed using theory, evidence, and a person-based approach. The optimization work suggests that practitioners may find this tool to be useful in supporting the reduction of long-term antidepressant use. Further quantitative and qualitative evaluation through a randomized controlled trial is needed to examine the feasibility, effectiveness, and cost-effectiveness of the intervention.